2010
DOI: 10.1098/rspb.2010.0965
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary rates of mitochondrial genomes correspond to diversification rates and to contemporary species richness in birds and reptiles

Abstract: Rates of biological diversification should ultimately correspond to rates of genome evolution. Recent studies have compared diversification rates with phylogenetic branch lengths, but incomplete phylogenies hamper such analyses for many taxa. Herein, we use pairwise comparisons of confamilial sauropsid (bird and reptile) mitochondrial DNA (mtDNA) genome sequences to estimate substitution rates. These molecular evolutionary rates are considered in light of the age and species richness of each taxonomic family, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 36 publications
11
110
2
1
Order By: Relevance
“…First, given that turtles originated in the Early Mesozoic, it is plausible that the initial increase of disparity is the result of random or adaptive exploration of the available morphospace. Given that turtles have extended generation times relative to most invertebrates or small amniotes [75,76], it is furthermore plausible that evolutionary rates are lower for the group [77,78] and that this diversification therefore took place over an unusually prolonged time period and was only stopped by climatic cooling. On the other hand, the early diversification of turtles also coincides with the break-up of Pangaea, as already noted for other reptile groups [79][80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…First, given that turtles originated in the Early Mesozoic, it is plausible that the initial increase of disparity is the result of random or adaptive exploration of the available morphospace. Given that turtles have extended generation times relative to most invertebrates or small amniotes [75,76], it is furthermore plausible that evolutionary rates are lower for the group [77,78] and that this diversification therefore took place over an unusually prolonged time period and was only stopped by climatic cooling. On the other hand, the early diversification of turtles also coincides with the break-up of Pangaea, as already noted for other reptile groups [79][80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Higher substitution rates and greater rate heterogeneity may be driving factors, although rate heterogeneity among nuclear and mitochondrial genes has rarely been evaluated [35]. Mitochondrial data suffer from greater NT composition bias and site saturation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of a link between rates of molecular evolution and netdiversification has been reported (Barraclough and Savolainen, 2001;Jobson and Albert, 2002;Eo and Dewoody, 2010;Lancaster, 2010;Lanfear et al, 2010abut see Goldie et al, 2011 where no such link was found in mammals). However, none of these studies have conclusively shown that increased rates of molecular evolution are responsible for elevated rates of speciation.…”
Section: Towards a Synthesismentioning
confidence: 99%